Parresía: um castelo de cartas shakespeariano - Azevedo, Leon Idris Fernandes de (2018)
This master thesis discuss the concept of parrhesia as a conductive thread between two narratives, the Shakespearean tragedy and the political drama series House of Cards, specifically its American adaptation, produced by Beau Willimon for Netflix in 2013. The analysis of the Shakespearean tragedy focuses on the play Ricardo III, although it also benefits from occasional parallels with Macbeth and mentions to King Lear and Hamlet. This thesis proposes the hypothesis that a single discursive axis can explain Shakespearean atemporality and the political bond of aforementioned narratives due to an ethical root of speech: the concept of parrhesia. This Greek word, of wide significance in the Antiquity, was applied by Euripides, Plato and among others the historian Polybius, when he describes the keystones of Greek democracy. The concept of parrhesia recovered here is tied to the researches of Michel Foucault, in particular the studies shared in his last two courses at the Collège de France, published in The Government of Self and Others (2010) and The Courage of Truth (2011).